-1 = 1 LOL!!!

Level 1

STEP 1 : 1 = 1

STEP 2 : 1 = 1 \sqrt { 1 }

STEP 3 : 1 = 1 × 1 \sqrt { -1\times -1 }

STEP 4 : 1 = 1 × 1 \sqrt { -1 } \times \sqrt { -1 } or i × i i\quad \times \quad i

STEP 5 : 1= ( 1 ) 2 { \left( \sqrt { -1 } \right) }^{ 2 } or i 2 { i }^{ 2 }

STEP 6 : 1 = -1

Question : THE ERROR IS IN WHICH STEP?

STEP 3 STEP 2 STEP 4 STEP 5

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

a b = a × b \sqrt { ab } = \sqrt { a } \times\sqrt { b } is valid for only positive values of a and b

Exactly . I also did the same

Rama Devi - 6 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...